Practicum Student Counselor Identity Development Through the COVID-19 Pandemic - Joy Teles Oliveira; Sarah A Silveus (Teaching and Supervision in Counseling, 2023)
The process of developing a counselor identity is a complex task, and it starts as early as when a student first enrolls in a Master’s program. Within the events surrounding COVID-19, limited information is known about how that experience might have affected counseling students' professional identity development. Through Interpretive Phenomenological Analysis, we explored the counselor identity development process of Master’s-level counseling practicum students (n=6) during the events of the COVID-19 pandemic. Emerging themes indicated that students' experiences throughout the pandemic had a unique influence on their conceptualization of the practicum experience. Findings illustrated that these events slowed some aspects of counselor identity development (e.g., perceptions of counselor roles, systemic identity integration) while expediting other aspects (e.g., self-reliance). Implications for counselor educators, supervisors, and counseling programs are discussed.
Keywords: counselor identity development; COVID-19 pandemic; practicum students; counselor education; supervision